A physical activity program to mobilize older people: A practical and sustainable approach - Jancey, Jonine; Clarke, Ann; Howat, Peter; Lee, Andy; Shilton, Trevor; Fisher, John (Oxford University Press, 2008)
Purpose: Despite the documented benefits of physical activity, it remains difficult to motivate older adults to start and maintain regular physical activity. This study tested an innovative intervention for mobilizing older adults into a neighborhood-based walking program. Design and Methods: Researchers recruited a total of 260 healthy but insufficiently active adults aged 65 to 74 years and randomly selected from the Australian electoral roll from 30 Perth metropolitan neighborhoods. Social cognitive theory guided the design of the program. Researchers collected both qualitative and quantitative data to inform the development, together with ongoing process evaluation. Results: A total of 65% of participants completed the program. Their mean weekly walking time for recreation increased by about 100 min, and 80% of participants reported that they would continue to walk twice per week upon program completion. Implications: This practical program is potentially effective and sustainable with respect to mobilizing physically inactive older people.